Alegal : Biopolitics and the Unintelligibility of Okinawan Life - Shimabuku, Annmaria M. (Book collections on Project MUSE., 2019)
"Alegal traces the trans-Pacific biopolitics between a postwar American empire of military bases and postcolonial Japan that secured Okinawa as a U.S. military fortress. It shows how both managed sex in its base towns from 1945 to 2015, and elucidates the potential for Okinawan insurgency in response to this collaboration"--